2016
DOI: 10.1007/s00415-016-8076-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between i.v. thrombolysis volume and door-to-needle times in acute ischemic stroke

Abstract: Centralization of intravenous thrombolysis (IVT) for acute ischemic stroke in high-volume centers is believed to improve the door-to-needle times (DNT), but limited data support this assumption. We examined the association between DNT and IVT volume in a large Dutch province. We identified consecutive patients treated with IVT between January 2009 and 2013. Based on annualized IVT volume, hospitals were categorized as low-volume (≤24), medium-volume (25–49) or high-volume (≥50). In logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
2
15
0
2
Order By: Relevance
“…[18] DTNT≤60 was also more common in patients treated at larger hospitals. Hospitals with greater ischemic stroke admissions per year and greater volume of IV tPA treated patients per year [6, 8, 19] are more likely to treat within 60 minutes. Previous studies reported that hospitals that treat larger proportions of Black patients have better tPA administration rates for Blacks.…”
Section: Discussionmentioning
confidence: 99%
“…[18] DTNT≤60 was also more common in patients treated at larger hospitals. Hospitals with greater ischemic stroke admissions per year and greater volume of IV tPA treated patients per year [6, 8, 19] are more likely to treat within 60 minutes. Previous studies reported that hospitals that treat larger proportions of Black patients have better tPA administration rates for Blacks.…”
Section: Discussionmentioning
confidence: 99%
“…Linear regression analysis was performed to assess the association between weight modality and DNT, presented as regression coefficient (B) and corresponding 95% CI. In secondary analysis, we adjusted for baseline characteristics associated with outcomes (P < 0.1) except for the analysis related to the outcome DNT where we adjusted for variables known to have an association with the DNT: availability of a CT in the emergency room (ER), blood pressure above the threshold for IVT (>185/110 mmHg), NIHSS score at baseline, 22,23 onset-to-door time (defined as the time between stroke onset and patient arrival at the hospital) and for annual IVT-volume divided as follows: lowvolume ( 24), medium-volume (25-49), or highvolume (!50) as described previously, with low-volume as reference category. 24 In subgroup analyses we investigated if differences in methods within the EBW or the MBW group could have affected the association between weight modality and the outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in our study weight modality was not associated with DNT even after adjusting for factors such as IVT volume, CT availability on the ER, baseline NIHSS, and blood pressure above IVT threshold. 24,[29][30][31] Nevertheless, other unknown factors related to the DNT we could not adjust for could possibly explain this lack of an association.…”
Section: Discussionmentioning
confidence: 99%
“…Bu durumu, merkezimizin bulunduğu Aydın ilinin nüfusunun diğer çalışmaların yapıldığı illere oranla daha az olması, dolayısıyla hasta yoğunluğunun servislerde daha az olması ve hastalara daha hızlı müdahale edilebilmesi ile açıklayabiliriz. Bizim çalışmamız da dahil olmak üzere ülkemizde yapılan çalışmalarda (19,21,33) bildirilen Kİ zamanı; yurt dışındaki çalışmalarda (20,22) Sonuç olarak NINDS rt-PA, ECASS, ECASS II, ATLANTIS çalışmalarının dâhil edildiği havuz analizinde erken zaman diliminde tedavi alanların, iyileşme yönünde daha yüksek şansa sahip olduğu anlaşılmaktadır (25). Çalışmamızda; Sİ zamanı ile NIHSS' da ki düzelme arasındaki ilişki incelendi ve orta derecede negatif bağıntı saptandı.…”
Section: Discussionunclassified
“…Tedavinin %10'u bolus olarak ve geri kalan kısmı bir saat içinde infüzyon olarak verildi. Ayrıca 3-4.5 saat aralığında olan iskemik inme hastaları için ek göreceli uygulamama kriterleri dikkate alındı (7 Tüm hastalar birlikte değerlendirildiğinde NIHSS ortalaması; başvuru esnasında 12±4 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), tedaviden sonra yirmi dördüncü saatte 8±7 (0-22) hesaplandı. Kaybedilen hastaları çıkardığımızda ise NIHSS ortalaması tedaviden önce 11±4 (3-18), tedaviden sonra yirmi dördüncü saatte 5±5 (0-18), taburculuk sırasında ise 3±5 (0-18) olarak belirlendi.…”
Section: Introductionunclassified